Causal relationship between gut microbiota and urticaria: a bidirectional two-sample mendelian randomization study - Shi, Yun-Zhou; Tao, Qing-Feng; Qin, Hai-Yan; Li, Ying; Zheng, Hui (Frontiers in Microbiology, 2023)
Background: Cumulative evidence showed an association between gut microbiota and urticaria, but the causal relationship between them is unclear. We aimed to verify whether there is a causal relationship between the composition of gut microbiota and urticaria and explore whether the causal effect was bidirectional. Methods: We obtained genome-wide association studies (GWAS) summary data of 211 gut microbiota and urticaria from the most extensive available GWAS database. A bidirectional two-sample mendelian randomization (MR) study was used to test the causal relationship between the gut microbiota and urticaria. The MR analysis was primarily performed with the inverse variance weighted (IVW) method, and MR-Egger, weighted median (WM), and MR-PRESSO were performed as sensitivity analyses. Results: The Phylum Verrucomicrobia (OR 1.27, 95%CI 1.01 to 1.61; p=0.04), Genus Defluviitaleaceae UCG011 (OR 1.29, 95%CI 1.04 to 1.59; p=0.02), and Genus Coprococcus 3 (OR 1.44, 95%CI 1.02 to 2.05; p=0.04) was a risk effect against urticaria. And Order Burkholderiales (OR 0.68, 95%CI 0.49 to 0.99; p=0.04) and Genus Eubacterium xylanophilum group (OR 0.78, 95%CI 0.62 to 0.99; p=0.04) were negatively associated with urticaria, suggesting a protective effect. At the same time, urticaria had a positively causal effect on gut microbiota (Genus Eubacterium coprostanoligenes group) (OR 1.08, 95%CI 1.01 to 1.16; p=0.02). These findings showed no influence by heterogeneity or horizontal pleiotropy. Moreover, most sensitivity analyses showed results consistent with those of IVW analysis. Conclusion: Our MR study confirmed the potential causal relationship between gut microbiota and urticaria, and the causal effect was bidirectional. Nevertheless, these findings warrant further examination owing to the unclear mechanisms.